Relationship Between Zinc Supply and Phosphorus Nutrition/ Phosphatase Enzyme Activity in a Hydroponically Grown Tomato Seedlings - Cengiz Kaya; David Hıggs; Agneta Burton (Journal of Agricultural Sciences)
Tomato Lycopersicon esculentum MIK cultivar Moneymaker, was grown hydroponically in controlled temperature C.T. room for 25 days to investigate relationships between phosphorus concentration in leaves and roots with phosphatase enzyme activity in relation to zinc supply. Zinc was added at concentrations of 0.05, 0.5, 1 and 2 mg/L in complete nutrient solution. The 2 mg/L zinc treatment resulted in a reduction in dry weights compared with other treatments, but there were no signifı cant differences in dry weights of seedlings between the other treatments. Zinc concentration in the plant increased with increasing zinc supply and reached a detrimental level with 2 mg/L Zn. However, there were signif ı cant decreases in P concentration in the leaves with increasing Zn supply and this decreased to an inadequate level in 2 mg/L Zn treatment. Phosphorus concentration in root increased with increasing Zn supply. Phosphatase enzyme activity was highest in the highest zinc treatment, with no significant differences in the activity in the other treatments.